Head injuries in children's football - results from two prospective cohort studies in four European countries - Faude, O.; Rössler, R.; Junge, A.; aus der Fünten, K.; Chomiak, J.; Verhagen, E.; Beaudouin, F.; Dvorak, J.; Feddermann-Demont, N. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Head injuries are considered harmful in children. We analysed head and neck injuries in organised football in 7 to 12 year old children. Data for this analysis were obtained from a prospective cohort study over two consecutive football seasons in two European countries, and a randomised intervention trial over one season in four European countries. Football exposure and injuries were documented through an online database. Detailed information regarding injury characteristics and medical follow-up was retrieved from coaches, children and parents by phone. Thirty-nine head injuries and one neck injury (5% of all 791 injuries) were documented during 9,933 player-seasons (total football exposure 688,045 h). The incidence was 0.25 [95%CI 0.15, 0.35] head/neck injuries per 1,000 match hours (N=23 match injuries) and 0.03 [95%CI 0.02, 0.03] per 1,000 training hours. Eleven concussions (27.5%), nine head contusions (22.5%), eight lacerations or abrasions (20%), two nose fractures (2.5%) and two dental injuries (2.5%) occurred. The remaining eight injuries were nose bleeding or other minor injuries. Thirty injuries (75%) resulted from contact with another player, ten injuries were due to collision with an object, falling or a hit by the ball. Whereas 70% of all head injuries (N=28) were due to frontal impacts, 73% of concussions (N=8) resulted from an impact to the occiput. The incidence and severity of head injuries in children's football is low. Coaches and parents, however, should be sensitised regarding the potential of concussions, particularly after an impact to the occiput.